THE The Future of Entrepreneurship in Indonesia: Fostering The Millennials' Entrepreneurial Intention - Elkana Timotius (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
Employment opportunities are unbalanced due to the addition of workers each year. Without proper management, this condition may increase unemployment, burdening the country's economy. Therefore, the entrepreneurial intention needs to be fostered for millennials to overcome the intense competition in the labor market. This quantitative study aims to identify the factors that influence the millennial's entrepreneurial intention in Indonesia in order to foster them appropriately. The survey was conducted in May-June 2021, involving 100 randomly selected respondents aged between 25 and 40 in Indonesia. A questionnaire with twenty-six questions was used to identify the right strategy for fostering entrepreneurial intention among millennials. Entrepreneurial knowledge, entrepreneurial orientation, and entrepreneurial efficacy were the three independent variables in this study. They were mediated by the entrepreneurial mindset on entrepreneurial intention as the dependent variable in path analysis, with family support as the moderating variable. Moreover, fifteen hypotheses were tested and accepted by statistical analysis using SmartPLS. The results showed that entrepreneurial knowledge, entrepreneurial orientation, and entrepreneurial efficacy affected the formation of the entrepreneurial mindset, influencing the growth of entrepreneurial intention. Furthermore, family support strengthened the effect of each relationship between these variables. However, family support could be limited by the millennials' unique characteristics and psychological development. Keywords: entrepreneurial knowledge, entrepreneurial orientation, entrepreneurial efficacy, entrepreneurial mindset, millennial's entrepreneurship